2010
DOI: 10.1111/j.1399-3054.2009.01312.x
|View full text |Cite
|
Sign up to set email alerts
|

Putative function of cytochrome b559 as a plastoquinol oxidase

Abstract: The function of cytochrome b559 (cyt b559) in photosystem II (PSII) was studied in a tobacco mutant in which the conserved phenylalanine at position 26 in the beta-subunit was changed to serine. Young leaves of the mutant showed no significant difference in chloroplast ultra structure or in the amount and activity of PSII, while in mature leaves the size of the grana stacks and the amount of PSII were significantly reduced. Mature leaves of the mutant showed a higher susceptibility to photoinhibition and a hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 59 publications
0
31
0
Order By: Relevance
“…Moreover, in the psbO-1 mutant, Murakami et al (2002) found that the fluorescence level transiently dropped below the F 0 level during illumination, similar to what we saw in the lto1 mutant (Figure 4). This phenomenon is not limited to psbO mutants, as it was also seen recently with mutants in the cytochrome b 559 subunit of PSII (Bondarava et al, 2010). One possibility is that the PQ pool is partially reduced in the dark in the lto1 mutant and in other mutants with low PSII activity, which would result in an increased F 0 level.…”
Section: The Redox Activity Of Lto1 Is Required For the Assembly Of Psiimentioning
confidence: 74%
“…Moreover, in the psbO-1 mutant, Murakami et al (2002) found that the fluorescence level transiently dropped below the F 0 level during illumination, similar to what we saw in the lto1 mutant (Figure 4). This phenomenon is not limited to psbO mutants, as it was also seen recently with mutants in the cytochrome b 559 subunit of PSII (Bondarava et al, 2010). One possibility is that the PQ pool is partially reduced in the dark in the lto1 mutant and in other mutants with low PSII activity, which would result in an increased F 0 level.…”
Section: The Redox Activity Of Lto1 Is Required For the Assembly Of Psiimentioning
confidence: 74%
“…On the contrary, cyclic electron transfer (CET) involves only one photosystem and occurs around either PSII or PSI (Shikanai, 2007;Bondarava et al, 2010;Johnson, 2011;Shinopoulos and Brudvig, 2012). Despite active research, the molecular mechanisms and biological functions of CETs are still largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Next, 1 O 2 is thought to stimulate the degradation of D1 protein (Asada and Takahashi, 1987;Krieger-Liszkay, 2005;Hideg et al, 2007;Gill and Tuteja, 2010;Vass, 2011). In addition to 1 O 2 , recent studies have revealed that superoxide (O 2 -) is also produced by PSII, which also causes photoinhibition (Bondarava et al, 2010;Zulfugarov et al, 2014). In contrast to the theory that oxidative degradation of the D1 protein causes photoinhibition in PSII, several studies now suggest that reactive oxygen species (ROS) suppress de novo D1 protein synthesis through the oxidative inactivation of the thioredoxin-regulated elongation factor G. The latter plays an important role in protein translation of the D1 protein (Kojima et al, 2007;Nishiyama et al, 2011).…”
mentioning
confidence: 99%